Maximizing opportunities for co-implementing fuel break networks and restoration projects - Aparício, Bruno A.; Ager, Alan A.; Day, Michelle A. (Frontiers in Forests and Global Change, 2024)
Increasing impacts from wildfires are reshaping fire policies worldwide, with expanded investments in a wide range of fuel reduction strategies. In many fire prone regions, especially in the Mediterranean basin, fuel management programs have relied on fuel break networks for decades to facilitate fire suppression and reduce area burned and damage. By contrast, in on the fire prone federal forests in the western US, fuel management is guided primarily by landscape restoration goals, including improving fire resiliency such that wildfires can be managed for ecological benefit, and suppression is used more as a tool to shape burn patterns and less to extinguish fires. New policies in both fire systems are now calling for hybrid approaches that rely on both types of investments and efficient allocation of the alternative spatial treatment patterns:, linear networks versus patches across the landscape. However, studies that combine these strategies and examine alternative co-prioritization strategies outcomes and potential synergies are largely non-existent. Here, we analyzed scenarios for implementing both types of treatments in concert while varying the prioritization metrics for one type or the other on a western US national forest. We measured the response related to both treatment strategies including fire intersection rate, improvement in forest resiliency, and net revenue. We found that projects with benefits to both strategies can be identified and mapped independently of the implementation scenario and restoration objective. However, scenarios prioritized for fuel breaks preceding restoration resulted in the identification of more projects that met the criteria for providing dual benefits. The study is a rare example of optimizing hybrid fuel treatment projects that serve both restoration and fire protection goals with different spatial treatment designs.